Fabrication of carbon paper containing PEDOT:PSS for use as a gas diffusion layer in proton exchange membrane fuel cells. (April 2015) - Kim, Hyunuk; Lee, Young-Ju; Park, Gu-Gon; Park, Seok-Hee; Choi, Yoon-Young; Yoo, Yoonjong
Abstract: Carbon papers (CPs) with high electrical conductivities and gas permeabilities have been historically used as gas diffusion layers (GDLs) in proton exchange membrane fuel cells (PEMFCs). CPs with high electrical conductivities are fabricated by the high temperature carbonization of a thermosetting resin, which acts as a binder and makes the CPs brittle to bending. Herein, we report the fabrication of CPs containing a conducting polymer poly(3, 4-ethylene dioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) under mild fabrication conditions. These CPs were prepared by combining pristine CP and PEDOT:PSS solutions with ethylene glycol (EG) and graphite powder (GP) and annealing the mixture at 100 °C. The CP containing PEDOT:PSS-EG-GP possessed an electrical conductivity higher than that of conventional CPs that were fabricated by high-temperature carbonization of a thermosetting resin. The mechanical stability of the CPs containing PEDOT:PSS-EG-GP was much higher than that of conventional CPs because of the flexibility of the conducting polymer. Moreover, the novel CP maintained its electrical conductivity after bending. We evaluated the performance of a single-cell for used as a PEMFC in which the GDL was a CP containing PEDOT:PSS-EG-GP.